IgA nephropathy: an overview of drug treatments in clinical trials. (2nd December 2022) - Selvaskandan, Haresh; Gonzalez-Martin, Guillermo; Barratt, Jonathan; Cheung, Chee Kay
ABSTRACT: Introduction: IgA nephropathy (IgAN) is the commonest primary glomerulonephritis worldwide and may progress to end-stage kidney disease (ESKD) within a 10–20 year period. Its slowly progressive course has made clinical trials challenging to perform, however the acceptance of proteinuria reduction as a surrogate end point has significantly improved the feasibility of conducting clinical trials in IgAN, with several novel and repurposed therapies currently undergoing assessment. Already, interim results are demonstrating value to some of these, offering great hope to those with IgAN. Areas covered: This review explores the rationale, candidates, clinical precedents, and trial status of therapies that are currently or have recently been evaluated for efficacy in IgAN. All IgAN trials registered with the U.S. National Library of Medicine; ClinicalTrials.gov were reviewed. Expert opinion: For the first time, effective treatment options beyond supportive care are becoming available for those with IgAN. This is the culmination of commendable international efforts and signifies a new era for those with IgAN. As more therapies become available, future challenges will revolve around deciding which treatments are most appropriate for individual patients, which is likely to push IgAN into the realm of precision medicine.